Perbedaan Komunikasi Interpersonal Anak-Orangtua Ditinjau Dari Keharmonisan Perkawinan Orang Tua - Veronika Suhartati (University of Merdeka Malang, 2015)
The survey is done in order to know any differences of interpersonal communication between parents and children from harmonious parent point of view. Data collecting process of this survey used interpersonal communication Likert scale. The result of the reliabilities of experiment in the substance of interpersonal communication is 0,946. The survey that is done gave the result that the average score of interpersonal communication of harmonious family is 2.6102 and the inharmonious family that is 2.0312. The Conclusion is that there are any differences interpersonal communication between parent and children in viewing of harmonious parent. Interpersonal communication of harmonious family is better than inharmonious family.